Organocatalytic Desymmetrization of Meso‐Aziridines Via Asymmetric Intramolecular Rearrangement. Issue 33 (9th July 2021) - Costanzo, Martina; Cortigiani, Mauro; Gillick‐Healy, Malachi W.; Kelly, Brian G.; Monasterolo, Claudio; Adamo, Mauro F. A.
Abstract: Herein we report the first organocatalytic method for the desymmetrization of meso ‐aziridines that does not require the use of an external nucleophilic reagent. The process was designed upon a base promoted rearrangement of bicyclic meso ‐cyclopentanone aziridines, that progresses in intramolecular fashion to provide densely functionalized cyclic ketones, key intermediates for the preparation of Active Pharmaceutical Ingredients. The key enantio‐determining step proceeded under the catalysis of a bifunctional thiourea organocatalyst. The process provides an entry to a class of highly functionalized chiral amines, 4‐aminocyclopentenones, not accessible with previous desymmetrization methods. The ambiphilic nature of the products makes them versatile synthetic intermediates in the preparation of natural products and popular antiviral nucleoside inhibitors, for example abacavir. Abstract : Enantioenriched N ‐tosyl‐4‐aminocyclopentenone, a key synthon for the preparation of natural products and many nucleoside inhibitors, was obtained via a new ring‐opening of a strained aziridine in high yields and in moderate (up to 74 % ee, 87 : 13 er) enantioselectivity.